Tackling the ST elevation in leptospirosis: A double-edged sword between bleeding and thrombosis – A case report - Dewi, Ivana P.; Damayanti, Kadex RS.; Anggitama, Andreas M.; Bagaskara, Arya T.; Dewi, Kristin P.; Yusrizal, Teuku (Narra Sains Indonesia, 2025)
Although leptospirosis is a well-recognized zoonotic disease, the occurrence of ST-segment-elevation myocardial infarction (STEMI)-mimicking leptospiral myocarditis, accompanied by subsequent bleeding and thrombocytopenia is an exceptionally rare finding. The dual risks of bleeding and thrombosis further complicate the management of anticoagulation and thrombolytic therapy amidst competing risks. The aim of this study was to present leptospirosis complicated by myocarditis, which mimicked STEMI, followed by bleeding and thrombocytopenia. A 61-year-old male patient was referred from a community health center to the hospital with primary complaints of chest discomfort and diaphoresis, which had started 11 hours prior to admission. These symptoms were associated with a 12-day history of intermittent fever, nausea, and vomiting. Upon physical examination, the patient appeared lethargic, with a blood pressure of 86/63 mmHg, heart rate of 107 bpm, respiratory rate of 22 breaths per minute, and temperature of 39.8°C. Electrocardiography revealed widespread ST-segment elevation. Echocardiography showed global hypokinesia with a reduced ejection fraction of 48%. Laboratory tests confirmed the presence of IgM and IgG anti-Leptospira antibodies, along with elevated high-sensitivity cardiac troponin levels. The patient was diagnosed with Weil's disease (Faine's score 32), with leptospiral myocarditis and STEMI considered as differential diagnoses. Initial management involved a loading dose of dual antiplatelet therapy (aspirin 320 mg and clopidogrel 300 mg) due to the suspected diagnosis of STEMI. However, it was later discontinued on the second day of admission due to the development of severe thrombocytopenia and minor bleeding manifestations. Following the administration of ceftriaxone 2 g every 12 hours and doxycycline 100 mg every 12 hours, the patient's condition improved. This case highlights the importance of recognizing leptospirosis as a potential cause of myocarditis and thrombocytopenia, especially when clinical signs resemble those of STEMI. Early diagnosis and careful management, including the suspension of dual antiplatelet therapy and initiation of targeted antibiotic therapy, were pivotal in preventing further complications and improving the patient's outcomes.